THE EMPLOYMENT OF A LANGUAGE EXCHANGE WEBSITE FOR TANDEM LANGUAGE LEARNING: EFL LEARNERS’ VIEWPOINTS - Fatimah, Siti (Universitas Gunadarma, 2015)
Benefits of tandem language learning have been exposed by some researchers. Conventional tandem exchange language learning usually requires two native speakers to meet face-to-face in order to learn each other’s language. Yet, it is not that easy to find native speakers to practice with. The aims of this study are to investigate whether a particular language website (italki) is capable to facilitate tandem language learning in distance language education (DLE) based on EFL (English as a Foreign Language) learners’ viewpoints, to find out whether the language exchange activity provides opportunity for negotiation of meaning and lastly, to investigate the strengths and weaknesses of the website. 10 participants majoring English at university level were involved in this study. They were given questionnaire to examine their viewpoints on the language exchange website. The result shows that italki is user-friendly and has helpful language learning features. Negotiation of meaning also occurs in one-to-one e-tandem language exchange activity. The most significant weaknesses of italki is the lack of chat features, so learners need to use other social media (Facebook, Twitter, etc) or applications (Skype, etc) to chat with native speakers. Regardless of its weaknesses, italki is capable to facilitate tandem language learning since it helps learners to find and connect with native speakers easily without requiring them to meet face-to-face. Keywords: Tandem language learning, Language exchange website, Distance Language Education (DLE), Native speaker, Viewpoints